Is Saglin a mosquito salivary gland receptor for Plasmodium falciparum? - David A. O’Brochta; Robert Alford; Robert Harrell; Channa Aluvihare; Abraham G. Eappen; Tao Li; Sumana Chakravarty; B. Kim Lee Sim; Stephen L. Hoffman; Peter F. Billingsley (Malaria Journal, 2019)
Abstract Background Saglin, a 100 kDa protein composed of two 50 kDa homodimers, is present in the salivary glands of Anopheles gambiae and has been considered an essential receptor for sporozoites (SPZ) of Plasmodium berghei and Plasmodium falciparum (Pf), allowing SPZ to recognize, bind to, and infect mosquito salivary glands. Spatial and temporal patterns of Saglin expression reported here, however, suggest that this model does not fully describe the Saglin–SPZ interaction. Results Saglin protein was detected by indirect immunofluorescence microscopy only in the medial and proximal-lateral lobes, but not in the distal-lateral lobes, of the salivary glands of An. gambiae; the pattern of expression was independent of mosquito age or physiological state. These results were confirmed by steady-state Saglin transcript and protein expression using qRT-PCR and Western-blot analysis, respectively. Saglin was localized to the basal surface of the cells of the medial lobes and was undetectable elsewhere (intracellularly, on the lateral or apical membranes, the cells’ secretory vacuoles, or in the salivary duct). In the cells of the proximal lateral lobes of the salivary glands, Saglin was distinctly intracellular and was not localized to any of the cell surfaces. Transgenic Anopheles stephensi were produced that expressed An. gambiae Saglin in the distal lateral lobes of the salivary gland. Additional Saglin expression did not enhance infection by PfSPZ compared to non-transgenic siblings fed on the same gametocyte-containing blood meal. Conclusions The absence of Saglin in the distal lateral lobes of the salivary glands, a primary destination for SPZ, suggests Saglin is not an essential receptor for Plasmodium SPZ. The lack of any correlation between increased Saglin expression in the distal lateral lobes of the salivary glands of transgenic An. stephensi and PfSPZ infection is also consistent with Saglin not being an essential salivary gland receptor for Plasmodium SPZ.